Respuesta :
First find the slope(m)
Slope= y2-y1/x2-x1= (1-(-5))/(-1-(-2))= 6/1 = 6
Then find the y intercept (move up six and right one from (-1, 1) to get (0, 7)
The y-intercept is y=7
Now make the equation
Y= slope(x) + y-intercept
Y=6x+7
Slope= y2-y1/x2-x1= (1-(-5))/(-1-(-2))= 6/1 = 6
Then find the y intercept (move up six and right one from (-1, 1) to get (0, 7)
The y-intercept is y=7
Now make the equation
Y= slope(x) + y-intercept
Y=6x+7
Answer: y = 6x + 7
Step-by-step explanation:
We can use slope formula to find the slope of a line that passes through two points (x₁ , y₁) and (x₂ , y₂)
m = ∆y/∆x = y₂-y₁/x₂-x₁
Given points are: P(x₁ , y₁) = (-2, -5) and Q(x₂ , y₂) = (-1, 1)
Substituting these two known points in the slope formula, we have:
m = (1-(-5))/(-1-(-2)) = 1+5/-1+2 = 6/1 = 6
Now we can use the point-slope formula to write the equation of a line given a point on the line and the slope of the line:
m = 6 , given point P(x₁,y₁) = (-2, -5)
Formula = (y-y₁) = m(x-x₁)
(y-(-5)) = 6(x-(-2))
y+5 = 6x + 12
y = 6x + 12 -5
y = 6x + 7
Answer: y = 6x + 7